Use of Cancer Registry data to aid resource allocation for service planning - Hayes, Catherine (Health Service Executive, 2019)
The health system delivers preventive, promotive, curative and rehabilitative interventions through a combination of public health actions and health improvement activities and facilities that deliver personal health care [1]. Information is needed to track how health systems respond to increased inputs and improved processes, and the impact they have on health indicators. A common monitoring and evaluation framework developed across countries in association with WHO, shows how health inputs and processes (e.g. health workforce and infrastructure) are reflected in outputs (e.g. interventions and available services) that in turn are reflected in outcomes (e.g. coverage) and impact (morbidity and mortality) [1]. According to SláinteCare there is a strong case for pooled budgets across primary and social care to support integrated care. “A resource allocation model is required that allows for equity of access to health services across different geographic areas, taking into account population need, demographics, deprivation and other measures. Ideally, it should relate funding to all aspects of care within a specific area”. It recommends that this is done via “Development and utilisation of a Geographic Resource Allocation Formula to ensure the equitable allocation of resources based on both population characteristics and activity level”. The alignment of Community Health Organisations (CHOs) and Hospital Groups is set out as one of the fundamental principles underpinning the healthcare reforms in the SláinteCare Report. The new nine Community Health Organisations (CHOs) will consist of 96 Community HealthCare Networks (CHNs), each of which will provide health and social care services to approximately 50,000 people. The CHN is recommended as the fundamental unit for organisation for the delivery of services. Each CHO will have an average of 10 CHNs to support groups of Primary Care Teams. A Primary Care Team (PCT) is a multidisciplinary group of health and social care professionals who work together to deliver local accessible health and social services to a defined population of between 7,000-10,000 people determined by geographical boundaries and/or the practice population of participating general practitioners (GPs). A network is planned for every large town or district in the country. There will be nine model CHN ‘learning sites’ to allow design of a population based service for chronic diseases based on age, deprivation and local incidence and prevalence rather than average figures. The initial phase will involve piloting the management structure. A model of integrated care will be based on the learning derived from these nine sites. Document scope and purpose The purpose of this document is to review how Cancer Registry data might be incorporated into local area profiles and displayed as a tool for service planning and to monitor service improvement. Methodology A literature search on the use of cancer registry data for service planning was conducted. Information on international cancer registries was obtained from relevant websites and is not exhaustive. Key personnel consulted in the preparation of this document are listed in Appendix 1. The findings from the relevant cancer registries are presented separately below.
APPROVED
Keywords: Cancer; CANCER